Donor dan Jual Beli Darah untuk Transfusi: Perspektif Hukum Islam Respon Hukum Islam terhadap Praktik Donor dan Transfusi Darah serta Jual Beli Darah Untuk Transfusi dalam bingkai Hifd an-Nafs (Menjaga Jiwa) - Saini Saini (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
In principle, blood donation is a noble charity that can save the lives of many people. Humanitarian tragedies in the form of accidents, operations, etc., almost certainly require assistance and the availability of adequate blood. Such events should arouse the feeling and spirit of human solidarity. Unfortunately, information about the benefits of blood donation for humanity and health has not been well communicated. In the polar literature at-Turats found a chapter that specifically discusses the law of donors and blood transfusions. With the various honors of the principle of good deeds to others using the blood donor media, Muslims in general need a more detailed and systematic reconceptualization of the decisions of Syara' law related to the practice and dynamics of the medical world. Therefore, this research will answer the following problem formulations, (1) what are the views of the fuqaha on the law of blood donation?, (2) what are the views of the fuqaha on the law of blood transfusion? And (3) What is the law on buying and selling blood for blood transfusion needs? To answer some of the problem formulations above, the researcher uses a type of research that adopts some qualitative research techniques that are library research, namely reviewing and researching library sources, in the form of fiqh books by contemporary fiqh scholars related to the theme discussion. The data collection technique used by the researcher is documentation technique because this research is library research. After the data is collected, it is analyzed by following the mile and hiberman analysis model and added with content analysis. This study produced three answers as a follow-up to the problem formulation that was made at the beginning of the discussion. First, contemporary fiqh scholars differ on the law of blood donation. In ikhtiyar conditions, the law of blood donation is prohibited. Meanwhile, in an emergency, they agree that it is permissible. Second, blood transfusions are not allowed because blood is an unclean object. However, if you can save human life, then yes. Third, the law sells blood both to individuals and to foundations or banks. because it is very useful for humans to help the souls of fellow humans who need blood transfusions due to operations and accidents